The importance of RSV F protein conformation in VLPs in stimulation of neutralizing antibody titers in mice previously infected with RSV - Lori M. Cullen; Madelyn R. Schmidt; Trudy G. Morrison (Taylor & Francis Group, 2017)
Respiratory syncytial virus (RSV) is a significant respiratory pathogen but no vaccine is available. RSV infections present 2 major, unique problems. First, humans can experience repeated infections caused by the same virus sero-group indicating that protective memory responses to RSV infection are defective. Second, most people have been infected with RSV by age 5. Immune responses to these infections, while poorly protective, could impact the effectiveness of a vaccine. The goal of this study was to assess the generation of protective immune responses in mice previously infected with RSV by virus-like particle (VLP) vaccine candidates containing a stabilized pre-fusion form of the RSV F protein or a stabilized post-fusion F protein. We report that a single immunization of RSV-experienced animals with a stabilized pre-fusion F protein VLP stimulated high titers of neutralizing antibody while a single injection of a post-fusion F protein VLP or a second RSV infection only weakly stimulated neutralizing antibody titers. These results suggest that prior RSV infection can induce neutralizing antibody memory responses, which can be activated by pre-F protein VLPs but not by post-F protein VLPs or a subsequent infection. Thus the F protein conformation has a major impact on enhancing production of neutralizing antibodies in RSV-experienced animals. Furthermore, although both VLPs contained the same RSV G protein, the pre-F VLP stimulated significantly higher titers of total anti-G protein IgG than the post-F VLP in both naïve and RSV-experienced animals. Thus the F protein conformation also influences anti-G protein responses.